2018
DOI: 10.2209/tdcpublication.2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PRF and Allograft Use on Immediate Implants at Extraction Sockets with Periapical Infection —Clinical and Cone Beam CT Findings—

Abstract: Immediate implant placement can be successful, even at infected sites. The adjunctive effects of concomitant use of platelet-rich fibrin (PRF) and decalcified freeze-dried bone allografts (DFDBA) at periapically infected sites remains to be determined, however. The purpose of this prospective study was to investigate the effect of combined use of PRF and DFDBA on immediate implant survival at tooth extraction sites exhibiting periapical lesions. Implants were immediately placed in 8 patients under a standard c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 47 publications
1
17
0
2
Order By: Relevance
“…Regarding postoperative infection, our result is in agreement with Medikeri et al They found combined use of growth factors with pre-and postoperative broadspectrum antibiotics over a short time resulted in a higher implant survival rate in infected site. Hoaglin et al found that we can Prevent localized osteitis in mandibular third molar sites using platelet rich fibrin (14,15) . Results of the present study have a statisticvally non-significant difference in mean of facial edema during the postoperative three months, indicate that using MPM has significant effect on the postoperative edema following dental implant surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding postoperative infection, our result is in agreement with Medikeri et al They found combined use of growth factors with pre-and postoperative broadspectrum antibiotics over a short time resulted in a higher implant survival rate in infected site. Hoaglin et al found that we can Prevent localized osteitis in mandibular third molar sites using platelet rich fibrin (14,15) . Results of the present study have a statisticvally non-significant difference in mean of facial edema during the postoperative three months, indicate that using MPM has significant effect on the postoperative edema following dental implant surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, PRF, a platelet concentrate, was used as a source of growth factors to accelerate the initial stages of wound healing. 11 L-PRF is a second generation of autologous platelet concentration and a fibrin mesh consisting of leukocytes, growth factors, proteins, and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…To refer the whole effects to BAs could seem reasonable, yet some hypotheses suggest that the application of an L‐PRF membrane onto the graft in the TSs could have contributed to the graft and blood clot stabilization, retaining them within the walls of the IBD 32 in the early phases of the healing process and favoring the defect's healing also through a mechanism independent from the BAs’ biological properties. However, it is true that in meta‐analyses 9,33 EMD showed not to take advantage for IBDs healing from the simultaneous membrane application.…”
Section: Discussionmentioning
confidence: 99%